Transforming music pedagogy: integrating digital production tools into modern education - Lazarev, Sergiy; et al. (European Journal of Social Science Education and Research, 2026)
The use of digital software and technology has had a significant effect on how the modern music industry functions and produces music. This paper will examine how streaming services, digital audio work stations, social platforms affect the way money is made in the music industry, how music is produced, and how artists interact with their audience. This study uses an empirical method based on the International Federation of Phonographic Industries' annual reports detailing the trends of world-wide recorded music and it's segments. It also utilizes other academic papers and industry reports, which provide a comprehensive look at the music industries transition into being a digitally driven industry. The study analyzes the potential of digital transformation of music education and proves that the introduction of innovative teaching tools and methods contributes to the expansion of the conceptual vision of educational functionality, increasing its transparency, efficiency and adaptability. The key capabilities of digital technologies to increase the involvement and motivation of students, their creative growth, as well as to create an inclusive and dynamic educational environment, and to create the preconditions for effective exchange of experience on a global musical scale are considered. In general, this study has shown that digital platforms and software have been a major factor in the changes taking place in the music industry, leading to its transformation towards greater platform orientation and influence on new monetization models and new performance practices. It is proved that current trends in the development of digital education are aimed at personalizing learning, creativity and efficiency, which is achieved through the involvement of online collaboration, adaptive technologies, artificial intelligence and social networks. However, digitalization has created many challenges for all parties involved, including issues related to unequal distribution of income due to algorithms, dependence on these algorithms, and competition with artificial intelligence-generated content.
Keywords: musical art, music industry, online platform, interactive technologies, digitalisation, streaming, innovations in piano teaching, digital competencies of a musician-pedagogue.